2015
DOI: 10.1186/s12882-015-0108-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant malnutrition, inflammation, and atherosclerosis affect cardiovascular outcomes after kidney transplantation

Abstract: BackgroundMalnutrition, inflammation, and atherosclerosis (MIA) syndrome is associated with a high mortality rate in patients with end-stage renal disease. However, the clinical relevance of MIA syndrome in kidney transplantation (KT) recipients remains unknown.MethodsWe enrolled 1348 adult KT recipients. Recipients were assessed based on serum albumin, cholesterol, or body mass index for the malnutrition factor and C-reactive protein level for the inflammation factor. Any history of cardiovascular (CV), cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
2
20
0
1
Order By: Relevance
“…Malnutrition and inflammation form a vicious cycle, leading to the development of atherosclerosis, and this subsequently increases cardiovascular mortality in various populations. 26,27 Our combined analysis showed that elderly CAD patients with both low GNRI and high CRP levels were at a 5.5-fold higher risk of PAD. These results suggest that assessments of both nutritional and inflammatory status are required to improve the identification of elderly CAD patients with a high risk of advanced atherosclerosis.…”
Section: Yamada Et Al Examined Patients With Hemodialysis Andmentioning
confidence: 82%
See 1 more Smart Citation
“…Malnutrition and inflammation form a vicious cycle, leading to the development of atherosclerosis, and this subsequently increases cardiovascular mortality in various populations. 26,27 Our combined analysis showed that elderly CAD patients with both low GNRI and high CRP levels were at a 5.5-fold higher risk of PAD. These results suggest that assessments of both nutritional and inflammatory status are required to improve the identification of elderly CAD patients with a high risk of advanced atherosclerosis.…”
Section: Yamada Et Al Examined Patients With Hemodialysis Andmentioning
confidence: 82%
“…Recently, the concept of malnutrition–inflammation–atherosclerosis syndrome has been proposed. Malnutrition and inflammation form a vicious cycle, leading to the development of atherosclerosis, and this subsequently increases cardiovascular mortality in various populations . Our combined analysis showed that elderly CAD patients with both low GNRI and high CRP levels were at a 5.5‐fold higher risk of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Desigualdades no acesso ao transplante são comuns em todo o mundo e vários são os fatores causadores, entre eles estão características socioculturais, socioeconômicas, clínicas e geográficas 14,15 . Como um possível fator limitante para o Tx renal está o exame laboratorial conhecido como albumina sérica, sendo a albumina uma proteína de fase aguda negativa 16 . Estudos 17,18 têm mostrado que a hipoalbuminemia sérica pode ser interpretada como um marcador de desnutrição, comorbidades, inflamação e aterosclerose em pacientes com DRC.…”
Section: Discussionunclassified
“…Cardiovascular disease (CVD) is common in kidney transplant recipients (KTRs) and coronary artery disease (CAD) alone is an important cause of morbidity and mortality in this setting and it is characterized by unique inflammatory features . These are affected by both specific transplant‐related risk factors and previous exposure to uremic milieu .…”
Section: Introductionmentioning
confidence: 99%
“…These are affected by both specific transplant‐related risk factors and previous exposure to uremic milieu . As a consequence, the Framingham risk model underestimates CV risk in this population and a significant proportion of cardiac events actually occur in non‐diabetic patients without any traditional risk factor …”
Section: Introductionmentioning
confidence: 99%